Skarga o stwierdzenie nieważności małżeństwa czy prośba o jego unieważnienie? Refleksja kanonistyczno-duszpasterska na kanwie introductio causae - Góralski, Wojciech (Ius Matrimoniale, 2014)
At the time of rapid and numerous social changes at the turn of XX and XXI century it, not only serious lacks in knowledge of doctrine and church discipline regarding marriage, including its indissolubility, but also the overwhelming divorce friendly mentality have been noted, which applies to Catholics as well. No proper preparation to conclude marriage has been noticed too. These circumstances encourage conclusion of marriage recklessly, which reflects in its durability. The unfavorable factor of preserving marriage indissolubility is also disability to overcome first difficulties experienced in the marriage. The author indicates more and more popular phenomenon of filing motions to ecclesiastical church for dissolution of marriage and focuses on the necessity of their reasonable and lawful selection in the initial phase of court proceedings.